Preparing Young Minds for Industry 4.0: Challenges and Changes - Sarika Srivastava; Tiwari, Dr. Ajay (IJRDO- Journal of Educational Research, 2019)
The new generation stepping into the fourth Industrial Revolution will witness a dynamic transformation in all aspects. New wave of global technology will change the entire world. With emergence of technology in education sector will witness many fundamental changes, in near future; many scientific and social theories will not be able to match the depth and breathe of human perceptions. The students graduating by 2030 will make career in the fields that we are at this moment clueless. Employment sector in this new era will seek critical thinkers, problem solvers, and people who can interact across the globe. The problem in the future would not be the lack of job, but the shortage of skills that the new jobs will demand. Thinking of future just scares us how our future generation will fit in such an atmosphere as our education system still continues to equip our children with skills that will be very little or have no relevance in future. This paper sincerely attempts to draw the attention of Parents, Teachers, and school/Collages management and policy makers on the future needs of our young minds. What need to be done in our education process to meet the challenges and changes that industrial revolution4.0 will bring with it.